Neural correlates of delusional infestation responding to aripiprazole monotherapy: a case report - Ponson L (Dove Medical Press, 2015)
Laura Ponson,1,2 Frédéric Andersson,1 Wissam El-Hage1,2 1Université François-Rabelais de Tours, Inserm, Imagerie et Cerveau UMR U930, Tours, France, 2CHRU de Tours, Clinique Psychiatrique Universitaire, Tours, France Background: The pathophysiology and appropriate pharmacological interventions for delusional infestation remain unknown.Case presentation: Here, we report a case of primary delusional infestation successfully treated with aripiprazole. We performed functional magnetic resonance imaging (fMRI) to investigate brain structures and functional modifications. Before antipsychotic treatment, pre- versus post-treatment fMRI images revealed a marked increase in brain activation in the supplementary motor area (SMA).Conclusion: Our results highlight the efficacy and safety of aripiprazole in the treatment of delusional infestation and the possible role of SMA dysfunction in delusional infestation. Indeed, our results suggest that psychiatric improvement of delusional infestation is associated with normalization of brain activity, particularly in the SMA. Keywords: supplementary motor area, antipsychotics, fMRI